Fusion power in a future low carbon global electricity system. (March 2017) - Cabal, H.; Lechón, Y.; Bustreo, C.; Gracceva, F.; Biberacher, M.; Ward, D.; Dongiovanni, D.; Grohnheit, P.E.
Abstract: Fusion is one of the technologies that may contribute to a future, low carbon, global energy supply system. In this article we investigate the role that it may play under different scenarios. The global energy model ETM (originally EFDA TIMES Model) has been used to analyse the participation of fusion technologies in the global electricity system in the long term. Results show that fusion technologies penetration is higher in scenarios with stricter CO2 emissions reduction targets. In addition, investment costs and discount rates of fusion technologies are key factors for fusion implementation. Finally, the main competitors for fusion in future are Carbon Capture and Storage and fission technologies. Highlights: The role of fusion in the future global power system is modelled in ETM. Eight scenarios with different costs, GHG targets and discount rates are simulated. Fusion can play an important role in a decarbonized global power system. Keeping fusion technology competitive in terms of costs is key for its penetration. Main competitors for fusion are CCS and fission technologies.